Diagnosis and clinical significance of prostate calcification using computed tomography - Seong Cheol Kim; Tae Young Lee; Woocheol Kang; Hoyoung Bae; Ji Hyung Yoon; Sungchan Park; Kyung Hyun Moon; Sang Hyeon Cheon; Taekmin Kwon (Scientific Reports)
Abstract This study aimed to assess the exact location, size, and clinical significance of prostatic calcification using computed tomography (CT). We retrospectively analyzed data from 5,492 patients who underwent CT at the Department of Urology in our hospital between January 2010 and December 2020. After applying exclusion criteria (prostate cancer, post-prostatectomy, indwelling urethral catheter, severe artifacts, and software errors), 4,805 patients were included in the final analysis. Patient age, medical history, laboratory findings, and the International Prostate Symptom Score (IPSS) were collected, with linear regression used to identify predictors of IPSS. Of the 4,805 patients, 1,525 had no calcification, 285 had calcification with a Hounsfield unit (HU) < 100, and 2,995 had calcification with HU ≥ 100. The average age of patients with calcification was significantly higher than that of patients without calcification. Total IPSS scores were significantly elevated in the calcification group, particularly in those with calcifications of HU ≥ 100. The majority of calcifications were located in the central zone (79.3%), followed by the periurethral (48.6%) and transitional zones (42.0%). Only a small number of calcifications were observed in the peripheral zone (0.9%). Multivariate analysis revealed that both age and prostate calcification were significant predictors of urinary symptoms. CT can be effectively utilized to accurately assess the exact location, size, and number of prostate calcifications. Prostate calcification increases with age and is associated with worsened lower urinary tract symptoms.